AB0795 Tacrolimus therapy for refractory dermatomyositis and polymyositis. (23rd January 2014) - Tombetti, E.; Bozzolo, E.; Guglielmi, B.; Margherita, B.; Scotti, R.; Baldissera, E.; Sabbadini, M.G.
Abstract : Background: Dermatomyositis (DM) and polymyositis (PM) are systemic inflammatory diseases affecting skeletal muscles, skin and variable other organs (1). Steroids are the mainstay of DM and PM therapy, but a first-line immunosuppressive drug like methotrexate (MTX) or azathioprine (AZA) have to be added in case of steroid inefficacy or need of sparing steroids (2). Unfortunately an untrivial fraction of patients maintains active disease despite adequate first-line therapy (3). Second-line treatments utilised for refractory disease are intravenous immunoglobulins (IVIg), rituximab (RTX), cyclosporine (CYC), cyclophosphamide (CTX) and mycophenolate mophetil (MMF). Tacrolimus is a calcineurin inhibitor that has been successfully used in previous reports of interstitial lung disease (ILD) associated with DM/PM; in these patients it demonstrated a good efficacy in muscular involvement too (4-5). Objectives: To evaluate efficacy of second-line treatment with tacrolimus for refractory DM and PM. Methods: We retrospectivelly studied patients with DM or PM followed at our Center between 2007 and 2011. Tacrolimus has been used if clinically needed only in case of refractoriness to first-line drugs. We have analyzed disease response to therapy of patients treated with tacrolimus as second-line immunosuppressive drug. Results: 34 DM or PM patients entered in our study: 21 females and 13 males, median age 57 years. 20 patients suffered of DM ad 14 of PM. All of them received steroid therapy, while 28 needed one o more adjunctive drugs: 21 MTX, 10 AZA, 12 others (MMF, CYC, CTX o RTX) and 4 patients IVIg. 9 of our 34 patients (8 females and 1 male, mean age 41 years) received tacrolimus for disease refractory to steroid and at least one immunosuppressive drug (Fig 1). One of these has PM, while 8 have DM (one case of overlap DM with systemic sclerosis and systemic lupus erythematosus). 6 patients had ILD. 8 of these 9 patients had a satisfactory response to tacrolimus: 5 cases of complete remission (i.e. normalisation of CK, regression of skin involvement without signs of active ILD) and 3 of partial response (i.e. improvement of CK and skin involvement without progressive ILD). The patient suffering of overlap disease did not satisfied these response criteria but achieved disease stability. Severe adverse events were not observed during follow-up. One patient had a transient elevation of creatininemia, and another suffered from mild hand tremors. Conclusions: In our patients tacrolimus has shown a good efficacy in DM and PM refractory to first-line immunosuppressive drugs. Considering its good tolerability, we suggest that it may represents the drug of choice in patient resistant or intolerant to first-line immunosuppressive treatments. References: Dalakas M.C., Hohlfeld R. Polymyositis and dermatomyositis. Lancet 2003; 362: 971-82. Marie I., Mouthon L. Therapy of polymyositis and dermatomyositis. Autoimmun Rev. 2011; 11(1):6-13. Jaffe M. M., et al. Drug therapy of the idiopathic inflammatory myophaties: predictors of response to prednisone, azathioprine and methotrexate and a comparison of their efficacy. Am J Med 1993; 94: 379-87. Waite E. L., Madhok R. Tacrolimus – a potential therapy for polymyositis? Rheumathology 2009; 48: 858-859. Oddis C. V., et al. Tacrolimus in refractory polymyositis with interstitial lung disease. Lancet 1999; 353:1762-3. Disclosure of Interest: None Declared